2005
DOI: 10.2134/jeq2004.0398
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Variability of Soil Phosphorus in Relation to the Topographic Index and Critical Source Areas

Abstract: A measure of soil P status in agricultural soils is generally required for assisting with prediction of potential P loss from agricultural catchments and assessing risk for water quality. The objectives of this paper are twofold: (i) investigating the soil P status, distribution, and variability, both spatially and with soil depth, of two different first-order catchments; and (ii) determining variation in soil P concentration in relation to catchment topography (quantified as the "topographic index") and criti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
87
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(93 citation statements)
references
References 45 publications
2
87
0
Order By: Relevance
“…However, some authors note that these models may have limited generality (Thompson et al, 2006) or that unmeasured variables such as local management practices may be more important (Page et al, 2005). b Hydrological variables.…”
Section: Physical Data Describing the Environmentmentioning
confidence: 99%
“…However, some authors note that these models may have limited generality (Thompson et al, 2006) or that unmeasured variables such as local management practices may be more important (Page et al, 2005). b Hydrological variables.…”
Section: Physical Data Describing the Environmentmentioning
confidence: 99%
“…Robinson and Metternicht used three different techniques including Inverse Distance Weight (IDW), cokriging and spline methods for predicting the level of soil salinity, acidity and organic matter in South West of Australia and the results showed that the cokriging and spline methods were the best techniques for estimation of the soil salinity level and organic matter content. Results also showed that the IDW method was suitable for prediction of soil acidity level (Zare-Mehrjardi, 2010 and Dal Lake Catchment of Lesser Himalayas Robinson and Metternicht, 2006 Page et al (2005) investigated the soil P status, distribution, and variability, both spatially and with soil depth, of two different first-order catchments; and determined variation in soil P concentration in relation to catchment topography (quantified as the "topographic index") and critical source areas.…”
Section: Introductionmentioning
confidence: 99%
“…Tools such as the New York State (NYS) Phosphorus (P) Runoff Index (P-Index) were developed, e.g., [4,18,28,32] that support planners in creating farm level nutrient management plans (NMPs) and the risk assessment of P export from agricultural fields to streams [33]. However, there still exists a gap between the scientific understanding of processes controlling NPS nutrient transport in watersheds dominated by VSA hydrology and the tools used by watershed planners to determine these high-risk areas [4,9,14,22,34].…”
Section: Introductionmentioning
confidence: 99%